Numerical simulation of the impact of unsteady flows around impervious buildings - LOUKA, ANNA (author) (2022)
In the last few years, the climate crisis has been accelerating at a dizzying pace and poses an emergency threat to our planet. Rainfalls have transformed into intense downpours, and flash flooding, combined with the sea level rise, leads to a higher risk of inundation of densely populated coastal cities. Moreover, the melting of the permafrost can lead to significant landslides, triggering the generation of mega-tsunami waves. The latter can have a catastrophic impact, not only on the infrastructure but also on human life. Man-induced climate change is responsible for the increase in frequency and intensity of extreme natural events, such as tsunamis, floods, and storm surges. Recent research indicates that almost one-fourth of the world population lives at high-risk locations to at least 0.15m of inundation depths with a return period of 1 in 100 years. Therefore, the urge of implementing protection measures against unsteady flows is imperative. Undoubtedly, the involvement of engineers can play a pivotal role in order to analyze these flows in the built environment and provide sufficient coastal and building plans to ensure safety and reduce reconstruction costs. The behavior of the unsteady flow around a structure is not a well-understood topic and results in a lack of accuracy and reliability. More insights are required into the fluid-structure interactions to come up with a safe building design. In the present study, unsteady flows are generated using the dam-break technique in line with previous research. The Thesis aims to model, validate, and implement a simplified approach to analyze the complexity of the hydrodynamic behavior of unsteady flows around impervious buildings, with different orientations and blockage ratios. To do so, the research introduces a numerical simulation method of a dam-break wave, using the two-dimensional, and non-rotational shallow water equations. The Galerkin finite-element model is applied for the discretization of the solution on a limited domain. Initially, the flow of ...